RELATIONSHIP BETWEEN KNOWLEDGE, ACTION OF FAMILY IN DCB (DRAIN, CLOSE, AND BURY) PROGRAM, AND THE EXISTENCE OF EGGS OF AEDES AEGYPTI MOSQUITO ON OVITRAP IN KANDAI KENDARI, INDONESIA - Yunus, Reni; Rosanty, Anita (Public Health of Indonesia, 2016)
Background: Dengue Hemorrhagic Fever (DHF) is a contagious disease caused by the dengue virus infection through Aedes aegypti mosquito. DHF often causes epidemics and Extraordinary Events (EE) in tropical and subtropical regions, including Indonesia.Objective: This study aims to examine the relationship between knowledge and society action on the prevention of dengue with the amount of mosquitoes trapped in ovitrap in Kandai, Kendari, Indonesia.Methods: The research method was an observational study with cross sectional design. The research was conducted at Kandai village, Kendari on May to July 2014. It was 87 homes with 87 families were recruited as sample size for this study. Ovitrap was used inside and outside of their homes.Results: DCB family knowledge and the existence of Aedes sp mosquitoes eggs on ovitrap were analyzed and observed in this study. Chi square test showed that X2 count value (1.261) was less than X2 table value (3.814) at error level 5% (Î± = 0.05) indicated that Ha was rejected and Ho was accepted. Meanwhile, Chi square test for the action of the family about DCB and the existence of eggs Aedes sp mosquito on ovitrap showed that X2 count value (4.115) was greater than X2 table value (3.814) at the error level 5% (Î± = 0.05), indicated that Ho was rejected and Ha was accepted.Conclusions:"¨ It was concluded that (1) there was no  relationship between DCB family knowledge and the existence of Aedes sp mosquitoes eggs on ovitrap, and (2) there was a relationship between the action of family about DCB and the existence of aedes sp mosquitoes eggs on ovitrap in Kandai Kendari.